2017
DOI: 10.1371/journal.pntd.0005776
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Angiostrongylus cantonensis (Nematoda: Angiostrongylidae) in southern China and some surrounding areas

Abstract: Angiostrongylus cantonensis is of increasing public health importance as the main zoonotic pathogen causing eosinophilic meningitis or meningoencephalitis, which has been documented all over the world. However, there are very limited studies about its phylogeography and spread pattern. In the present study, the phylogeography of A. cantonensis in southern China (including Taiwan) and partial areas of Southeast Asia were studied based on the sequences of complete mitochondrial cytochrome b (Cytb) gene. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Following the introduction of the pet passport (European Union Regulation 998/2003) many of these dogs travel to/from Europe, creating opportunities to import different parasite strains and facilitating the spread of novel haplotypes throughout the UK. (Eamsobhana et al, 2013;Peng et al, 2017). The work described here reinforces the geographic split between Europe and North America, but reveals no notable geographic structure within European A. vasorum populations (Jefferies et al, 2009b).…”
Section: Discussionsupporting
confidence: 73%
“…Following the introduction of the pet passport (European Union Regulation 998/2003) many of these dogs travel to/from Europe, creating opportunities to import different parasite strains and facilitating the spread of novel haplotypes throughout the UK. (Eamsobhana et al, 2013;Peng et al, 2017). The work described here reinforces the geographic split between Europe and North America, but reveals no notable geographic structure within European A. vasorum populations (Jefferies et al, 2009b).…”
Section: Discussionsupporting
confidence: 73%
“…Significant variation ( P = 0.001) was found in the number of papers published on the different species of nematode found infecting A. fulica , with the largest number of papers referring to A. cantonensis (Chen, 1935), primarily in the countries of Asia ( n = 14) and South America ( n = 15). In Asia, A. fulica infected with A. cantonensis were recorded in Taiwan, Thailand, Japan, Malaysia, Indonesia, Philippines, China and Singapore (Lim & Heyneman, 1965; Bisseru, 1971; Stafford et al, 1976; Lv et al , 2009; Hu et al , 2011; Deng et al , 2012; Yang et al , 2012; Constantino-Santos et al , 2014a; Kim et al, 2014; Song et al, 2016; Peng et al , 2017) while in South America, this nematode has been recorded in Brazil, Colombia and Ecuador (Thiengo et al, 2010; Giraldo et al , 2019; Solórzano-Alava et al , 2019). Angiostrongylus cantonensis was also recorded in Cuba and Guadalupe ( n = 3) in the Caribbean (Vázquez & Sanchez, 2015; Dard et al , 2017), in Florida, ( n = 6) in North America (Smith et al, 2015) and in Hawai'i, in the Pacific Ocean ( n = 1), and in the Mariana Islands (Wallace & Rosen, 1969; Kim et al, 2014), Papua New Guinea (Scrimgeour & Welch, 1984), French Polynesia (Fontanilla & Wade, 2012) and Micronesia (Kim et al , 2014) in Oceania.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly ( P = 0.007) more studies were based on the collection of specimens during the daylight period ( n = 14 papers), in particular in South America (Moreira et al , 2013; Peng et al , 2017; Bechara et al , 2018; Ramos-de-Souza et al , 2018; Silva et al , 2020; Souza et al , 2021), with only five surveys being conducted at night (Lim & Heyneman, 1965; Morocoima et al , 2014; Cuasapaz-Sarabia, 2016; Peng et al , 2017; Bechara et al , 2018), and thirty-two studies did not specify the collection period (online supplementary file table S2). Five studies referred to the collection of specimens during the rainy season (Caldeira et al , 2007; Vitta et al , 2011; Andrade-Porto et al , 2012; Cuasapaz-Sarabia, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, gene flow is considered of fundamental importance, as it allows the exchange of genetic information between populations, homogenizing the variation among them [ 65 ]. Population genetic studies of parasitic helminths have shown that gene exchange between populations is strongly influenced by the movement of their vertebrate [ 17 , 22 ] and invertebrate hosts [ 66 ]. Aspidodera raillieti is a parasite with a monoxenous life cycle [ 10 ], depending on its mammalian hosts for dispersion.…”
Section: Discussionmentioning
confidence: 99%